Oz - The Complete First Season Episode 1-8 - Martin, Darnell; Gomez, Nick; Zakrzewski, Alex; Hudson, Ernie; Kinney, Terry; Perrineau, Harold (Paramount Pictures, 2009)
The Oswald Maximum Security Correctional Facility has opened an experimental new ward, Emerald City, reserved for especially dangerous criminals. Inside the walls of this rehabilitation unit, is a world that's even more corrupt and dangerous than the mean streets the inmates left behind. Survival is dependent on two sets of rules; those laid down by the warden and those understood by the racially divided prisoners. Gritty and violent, "Oz" deftly handles sensitive issues concerning the American justice system. [www.amazon.co.uk]
Keywords: DVD-Video